'Patient 0' and the Origin of HIV/AIDS in America. Issue 1 (January 2017) - Gong, Zhen; Xu, Xiaoyu; Han, Guan-Zhu
Abstract : The origin of the HIV/AIDS epidemic in North America remains contentious. A recent study uses phylogenetic and historical approaches to investigate the early history of HIV-1 group M subtype B in North America and shows that 'Patient 0' is not the source of the North American HIV/AIDS epidemic.